Shotgun weddings and bohemian dreams: Jazz, family values and storytelling in Australian film. (20th April 2015) - Coady, Christopher
Abstract : Recent research on jazz presence in Australian film has demonstrated how the genre was once used to enhance narratives about both the threats and the perceived benefits of impending modernisation during the 1920s and 1930s. This article charts out the way in which the musical trope of the bluesy solo horn – established in American and Australian film noir productions of the 1970s and 1980s – was used in contrast to conjure a sense of nostalgia in Australian films produced during the early 1990s. Despite pivoting a period of 60 years, analysis undertaken in this article of Gillian Armstrong's The Last Days of Chez Nous (1992) and Paul Harmon's Shotgun Wedding (1993) reveals the continued deployment of jazz sounds to rhetorical ends within Australian films bent on exploring competing societal visions. In turn, its identification of a shift from the sound of jazz in general as a marker of the modern to the sound of the bluesy solo horn as a nostalgic trope reinforces the need to read the semiotics of jazz presence in Australian film against particular historical frames.